Satisfaction with cultural/heritage sites: Virginia historic triangle - Huh, J.; Uysal, Muzaffer (2013)
This study attempted to investigate the relationship between cultural/heritage destination attributes and overall satisfaction, and to identify the difference in the overall satisfaction of tourists in terms of selected demographic and travel behavior characteristics. The expectancy-disconfirmation theory provided a conceptual framework for this study. This theory holds that consumers first form expectations of products or service performance prior to purchasing or use. The study area for this study was Virginia Historic Triangle (Williamsburg, Jamestown, and Yorktown). The survey was conducted at five different sites in the Virginia Historic Triangle. The findings indicate that there is a relationship between destination attributes and overall satisfaction with cultural/heritage experience. The study also reveals that overall satisfaction may show variation by gender, length of stay, and decision horizon. The study concludes with appropriate marketing and management implications.